The Influence Of Demographics And Financial Literacy On Investment Behavior With Risk Attitude Moderation In Bpkp Civil Servants - Fauzi, Achmad Zulfikar; Hanggraeni, Dewi (UNIVERSITAS PAKUAN, 2024)
This research aims to investigate the influence of demographic factors and financial literacy on risk attitudes and investment behavior among Civil Servants (PNS) of the Financial and Development Supervisory Agency (BPKP) as well as the moderating role of risk attitudes in this relationship. Data was collected from 272 BPKP civil servants and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The research results show that demographic factors such as age and educational background have a significant effect on risk attitude. Apart from that, age, gender and income level have a significant effect on investment behavior. Financial literacy is proven to have a positive and significant influence on risk attitude and investment behavior. Risk attitude also has a positive and significant influence on investment behavior. The moderating role of risk attitude is proven to be significant on the relationship between demographic factors and investment behavior, but not significant on the relationship between financial literacy and investment behavior. These findings provide important implications for financial managers and policy makers at BPKP to consider demographic factors and financial literacy in an effort to increase financial literacy and risk management among civil servants as well as encourage the development of more effective financial training programs and personalize investment strategies according to risk profiles. individual .